Censors Get Smart: Evidence from Psiphon in Iran. Issue 3 (13th February 2019) - Deibert, Ronald; Oliver, Joshua; Senft, Adam
Abstract: Information controls are actions intended to deny, disrupt, monitor, or secure information for political ends. They can be implemented using a wide variety of technical and nontechnical means. Political contests over the control of information are heightened around important events, such as major anniversaries, armed conflicts, protests, and elections. In this paper, we offer a comparative case study of online censorship of the circumvention tool Psiphon during the Iranian elections in 2016 and 2013, drawing on unique access to analytics data from Psiphon. We find that the Iranian regime developed its censorship approach in two ways, deploying blocking that was more targeted and strategically timed in the more recent case. Evidence suggests that the regime relaxed censorship of Psiphon during the official campaign period for the 2016 election. The apparent objective of this new approach was to control access to information while minimizing the political consequences of doing so. Abstract : 审查者变聪明：从伊朗赛风中得出的证据: 信息控制是出于政治目的，用于否认、扰乱、监控或确保信息的手段。信息控制可以通过使用一系列技术和非技术手段来实施。关于信息控制的政治竞争通过重要事件得以加强，例如主要纪念日、武装冲突、抗议和选举。通过从规避审查工具赛风（Psiphon）处提取的分析数据，笔者在本文中提供了有关2016年伊朗选举期间网络审查的案例研究。笔者将有关封锁方法和时间线的实证发现与关于2013年伊朗选举中使用赛风的先前研究进行比较，以检验假设——独裁政权会随着时间学习并适应其审查方式。本文结论认为，伊朗政权的确以两种方式发展了其审查方式，并在近期案例中运用了更具目标性和战略性时刻的网络封锁。 Abstract : Los censores se vuelven inteligentes: evidencia de Psiphon en Irán: los controles de información son acciones destinadas a negar, interrumpir, monitorear o asegurar información con fines políticos. Se pueden implementar utilizando una amplia variedad de medios técnicos y no técnicos. Las disputas políticas sobre el control de la información se acentúan en torno a eventos importantes, como los principales aniversarios, los conflictos armados, las protestas y las elecciones. En este documento, ofrecemos un estudio de caso de censura en línea durante las elecciones iraníes en 2016, que se basa en un acceso único a los datos analíticos de la herramienta de elusión Psiphon. Comparamos nuestros hallazgos empíricos con respecto a los métodos de bloqueo y el cronograma con la investigación previa en la herramienta Psiphon en las elecciones de 2013 en Irán para probar la hipótesis de que los regímenes autoritarios aprenden y adaptan su enfoque de censura con el tiempo. Nuestros hallazgos sugieren que el régimen iraní desarrolló su enfoque de censura de dos maneras, desplegando un bloqueo que fue más específico y más oportuno en el caso más reciente.